Impact of life style factors on lower urinary tract symptoms in Bahraini men - Abdulaziz Behzad, Alwaleed (International Journal of Research in Medical Sciences, 2025)
Background: This study aimed to evaluate the impact of lifestyle factors on lower urinary tract symptoms (LUTS) in Bahraini men, focusing on associations between demographic, clinical, and behavioral factors and LUTS severity. Methods: A cross-sectional study was conducted on 100 Bahraini men. The participants were grouped according to LUTS severity into mild, moderate, and severe categories. Data regarding age, smoking status, body mass index (BMI), hypertension, diabetes, stroke, depression, and osteoarthritis were collected. Chi-square tests and multivariate logistic regression were used to analyze the associations. Odds ratios (ORs) and 95% confidence intervals (CIs) were reported. Results: The prevalence of severe LUTS was highest among participants aged 60–69 years (50.0%) and ≥70 years (15.0%) compared to younger groups (p<0.001). The prevalence of severe LUTS was higher among current and former smokers, individuals with severe physical inactivity (OR=5.2; 95% CI, 2.4–11.3; p<0.001), obesity (OR=4.6; 95% CI, 2.1–10.1; p<0.001), and high stress (OR=5.9; 95% CI, 2.7–12.8; p<0.001). Chronic diseases were common, with diabetes (28.0%) and stroke (15.0%) showing strong associations (OR=7.4 and 8.6, respectively; both p<0.001). Conclusion: LUTS severity in Bahraini men is closely linked to aging, unhealthy lifestyle behaviors, and chronic comorbidities. Modifiable risk factors can be addressed to provide early intervention and symptom mitigation. Longitudinal research is recommended to confirm causal relationships.